1999
DOI: 10.1007/pl00005338
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nociceptin receptors in the periphery: in vitro and in vivo studies

Abstract: Nociceptin (NC), a series of NC fragments, naloxone as well as the pseudopeptide [Phe1psi(CH2-NH)Gly2]NC(1-13)NH2 ([F/G]NC(1-13)NH2) were used to characterize NC receptors in peripheral isolated organs and in vivo. Experiments on isolated organs were performed in the mouse (mVD) and rat (rVD) vas deferens (noradrenergic nerve terminals), in the guinea pig ileum (gpI; cholinergic nerves) and in the renal pelvis (gpRP; sensory nerves), and, in vivo, by measuring the blood pressure (BP) and heart rate (HR) in ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 18 publications
5
64
0
Order By: Relevance
“…However, there is now considerable evidence that each of these ligands can behave as pure antagonists Bigoni et al, 1999;Madeddu et al, 1999, Berger et al, 2000Malinowska et al, 2000b), partial agonists (Dooley et al, 1997;Bigoni et al, 1999;Berger et al, 2000;, or full agonists (Butour et al, 1998;Berger et al, 2000;Malinowska et al, 2000a;Olszewski et al, 2000) across different in vitro and in vivo systems (for review, see Calo' et al, 2000). The results of the present studies extend these observations and clearly demonstrate that these same NOP receptor ligands can display mixed pharmacological behavior from full/partial agonist to antagonist activity within a given biological system, in this case involving processes regulating cardiovascular and renal function in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is now considerable evidence that each of these ligands can behave as pure antagonists Bigoni et al, 1999;Madeddu et al, 1999, Berger et al, 2000Malinowska et al, 2000b), partial agonists (Dooley et al, 1997;Bigoni et al, 1999;Berger et al, 2000;, or full agonists (Butour et al, 1998;Berger et al, 2000;Malinowska et al, 2000a;Olszewski et al, 2000) across different in vitro and in vivo systems (for review, see Calo' et al, 2000). The results of the present studies extend these observations and clearly demonstrate that these same NOP receptor ligands can display mixed pharmacological behavior from full/partial agonist to antagonist activity within a given biological system, in this case involving processes regulating cardiovascular and renal function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are of interest considering that N/OFQ (30 or 100 nmol/kg) characteristically produces an immediate and marked bradycardia and hypotension after i.v. bolus injection in conscious or anesthetized rats Bigoni et al, 1999;Madeddu et al, 1999;Kapusta, 2000;Malinowska et al, 2000aMalinowska et al, , 2002. However, as partial agonists, it might be expected that these ligands are required to bind to and activate more receptors to elicit an equal response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vas deferens taken from Swiss or CD1/C57BL6/J-129 NOP +/+ and NOP −/− mice were prepared as previously described [4]. Tissues were continuously stimulated through two platinum ring electrodes with supramaximal voltage rectangular pulses of 1 msec duration and 0.05 Hz frequency.…”
Section: Electrically Stimulated Mouse Vas Deferensmentioning
confidence: 99%
“…Thus, N/OFQ relaxes vascular smooth muscle (Gumusel et al, 1997;Armstead, 1999;Champion et al, 1999) and when administered as an intravenous (i.v.) bolus to anesthetized (Champion and Kadowitz, 1997;Bigoni et al, 1999) or conscious (Giuliani et al, 1997;Madeddu et al, 1999;Kapusta, 2000) rats or mice, this peptide produces dose-dependent hypotensive and bradycardic responses. In addition, we have demonstrated that the continuous i.v.…”
mentioning
confidence: 99%